Website Penerimaan Siswa Baru Smp Persatuan Republik Indonesia (PGRI) Kota Pagaralam - Desi Puspita (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2017)
The new admissions website at SMP PGRI Pagaralam is still done manually, that is the acceptance of new students have not used the programming language, where the new student acceptance is still recorded in the big books, so the peroses of service on the acceptance of new students become slow and ineffective. Results and this study is a new admissions system that has been asked directly at SMP PGRI Pagaralam City. This system is built using Macromedia Dreamweaver CS3 application, programming languages ​​PHP and MySQL, while the system development method is Web ngineering. From the research it can be concluded that to create a new student admissions website that must be done first is to create a new admissions website. If the new admissions system is built is able to input new student admissions data and generate output in the form of reports then it can be concluded that the new admissions website SMP PGRI Pagaralam Pagaralam successful.